(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
High-performance electric Motors are in high demand due to the increasing need for production in all sectors. The brushless direct current motor is a promising future in most dynamic applications, such as the automotive, drone, rolling industries, and home appliances. The objective of this study was to design and manufacture a lightweight, high-thrust brushless DC motor that can reach high speeds suitable for drones and perform the necessary electrical analysis. The structure of the motor was designed using Solid Works software. Then, the designed motor was manufactured and tested. During the test, the current drawn by the motor was tested without load and using a three-blade propeller 18 x 8 inches. The number of revolutions per minute (RPM)was tested compared to the current drawn. It has been observed that the RPM increases rapidly with increasing motor current. As the motor’s performance testing continued, the motor’s thrust was checked based on the current drawn. As expected, the thrust increases gradually with the increase in the current drawn. Tests have been completed and the results have confirmed that the manufactured motor possesses all the expected features.